PENGARUH VARIASI LUAS PERMUKAAN PLAT ELEKTRODA DAN KONSENTRASI LARUTAN ELEKTROLIT KOH TERHADAP DEBIT GAS HASIL ELEKTROLISIS AIR - Susanto, Agustinus; Rubiono, Gatut; Bunawi, Bunawi (Virtual of Mechanical Engineering Article, 2016)
This   research   is   aimed   to   get   the   effect   of   electrode   surface   area   and   electrolyteconcentration  due  to  gas  volume  flow  rate  of  water  electrolysis.  The  surface  area  is  varied  as19.264 mm2, 38.528 mm2  and 57.792 mm2. The KOH electrolyte concentration is varied as 5 gram,10  gram,  15  gram,  20  gram,  and  25  gram  in  a  litre  aquades.  The  experiment  is  conduct  in  an electrolyzer.  HHO  gas  is  flowed  pass  trough  an  orifice  for  volume  flow  rate  measurement.  The research shows that the increase surface area and electrolyte concentration tend to increase gasvolume flow rate. The maximum gas volume flow rate happened at 57792 mm2  surface area and25 gram  KOH  electrolyte  concentration  which  is  0,00123  m3/det.  The  minimum  gas  volume  flow rate  happened  at  19264  mm2   surface  area  and  5  gram  KOH  electrolyte  concentration  0,00045 m3/det.